Costa Rican Protection of Statelessness under the Lens of International Human Rights Standards - Abarca Sánchez, Jesús Andrés (2026)
This work addresses the role of the Costa Rican State in the protection of the human rightsof persons in a situation of statelessness. It conducts a comparative analysis between CostaRica’s domestic laws and the framework of International Human Rights Law, complemented by the standards of the Inter-American Court of Human Rights, the Inter-American Commission on Human Rights, and the United Nations High Commissioner for Refugees (UNHCR).